GENETIC AND DEMOGRAPHIC FACTORS OF A BRAZILIAN POPULATION SAMPLE AT-RISK OF HEREDITARY BREAST AND OVARIAN CANCER - Guarneri, Guilherme Olivetti; Ponte, Bruno Jerônimo; Ferreira, João Henrique Fregadolli; Mitsutake, Leonardo Kenji Nesi; Guedes, Murilo Henrique; Casali-da-Rocha, José Cláudio (Mastology, 2018)
Objective: Genetic-related breast cancer has a tendency to manifest earlier and to be more aggressive than sporadic cancer. There are few studies evaluating the prevalence and incidence of hereditary breast and ovarian cancer (HBOC) among Brazilians. In order to improve assistance, efforts to characterize the population at risk of HBOC could help to formulate locally designed guidelines. Methodology: Descriptive retrospective study in Hospital Erasto Gaertner’s service of Oncogenetics, in Curitiba, state of Paraná, Brazil. We included individuals at-risk for HBOC, according to the National Comprehensive Cancer Network (NCCN) criteria, who had performed genetic tests for HBOC. We collected complete family history, presented as heredograms. We excluded families with inappropriate family history. Results: Of the 27 patients analyzed (total of 25 families), 7% were asymptomatic, 8% had ovarian cancer and 85% had breast cancer. Mutations were found in 29.6%, 6 cases of BRCA1, 1 of BRCA2 and 1 of TP53. Triple negative was the most common reported subtype, representing 60% of breast cancers; among patients with identified pathogenic variants, 2 were BRCA2 mutated and 1 TP53 mutated. The mean age of diagnosis was 40 years for those identified as probands on heredograms; in the generation above, it was 52,5, and in the below, 33, suggesting the antecipation phenomena Two new mutations were identified in Brazilian population, both in BRCA1: c.4258 G>A and c.5345 G>A. The most frequent NCCN criteria were number 2, 9, 8 and 4. Estimated penetrance was 22%. Conclusion: This is the first descriptive study in the population at-risk for HBOC in the state of Paraná. We could identify two new pathogenic variants of BRCA1 in Brazilian population. A comprehensive family history was included in the study, depicted as heredograms of each family. Despite the low number of patients, the main results are in agreement with previous studies.